Knowledge on The Risk of The Ischemic Heart Disease Estimation by WHO Charts in Cempaka Baru, Indonesia - Fitriani, Hasna Luthfiah; Ridwan, Karina Ajeng DA (Folia Medica Indonesiana, 2022)
Highlights: • The risk estimation of ischemic heart disease. • High blood pressure and cholesterol levels affect Ischemic heart disease. Abstract: In 2018, Indonesia became the country with the second-highest number of deaths and disabilities (DALYs) due to ischemic heart disease. Based on Riskesdas data in 2018, Jakarta is one of the provinces with a high percentage (1.9%) of ischemic heart disease. Risk factors for ischemic heart disease that are not treated quickly will increase the severity of ischemic heart disease in the future. Therefore, this study was to provide education regarding the assessment of risk estimation for ischemic heart disease with WHO/ISH charts among participants in Cempaka Baru sub-district. This study used pre-test and post-test questionnaires. After the seminars, the interview and examination results were carried out as well as calculating the estimated risk of ischemic heart disease using the WHO chart. These charts were divided into low risk (<10%), moderate (10-20%), and severe (>20%). The evaluation was conducted by comparing the pre-test and post-test results, which indicated that the knowledge level increased significantly from the Paired T-Test with a p-value = 0.000 (p<0.05). The significant estimation of high risk of ischemic heart disease for high blood pressure was 72.7% (p=0.023) and total cholesterol level was 66.7% (p=0.049). The increasing knowledge of the stratification risk of ischemic heart disease with the WHO chart was expected to reduce the risk of ischemic heart disease in the future.